The Role of Influencer Marketing and Sales Promotion on the Purchase Decision of Scarlett Whitening Products - Destri Mailinda Tianingrum; Ratih Hurriyati; Hilda Monoarfa (Prodi S1 Administrasi Bisnis Universitas Sangga Buana YPKP, 2024)
This research is a quantitative research that examines social phenomena with the aims to determine the effect of influencer marketing and sales promotion on purchase decision of scarlett whitening products. The population of this research is scarlett whitening consumers. This research took a sample of 100 respondents through a non-probability sampling technique using purposive sampling method. The data collection for this research was in the form of distributing questionnaires to consumers who had bought and used scarlett whitening products. The data analysis technique used is descriptive analysis and inferential analysis by the Partial Least Square (PLS) 3.0 analysis tool. The results of this research state that the influencer marketing has a significant effect on purchasing decisions and sales promotion has a significant effect on purchasing decisions. The implications of this research, can be a reference for business owners in determining a marketing multichannel system to increase sales of scarlett whitening products, especially in sales promotion and marketing through influencers.